2015
DOI: 10.3748/wjg.v21.i12.3554
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis-associated hepatocellular carcinoma in Chinese patients: Incidence and risk factors

Abstract: HCC is not rare in Chinese PBC patients. Risk factors for PBC-associated HCC include BMI ≥ 25 and a history of alcohol intake. In addition to regular monitoring, PBC patients may benefit from abstinence from alcohol and body weight control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…The annual incidence (%) of HCC in the non‐cirrhotic state (Scheuer's stage Ⅰ~Ⅱ) was 0.26% and that in the pre‐cirrhotic ~cirrhotic state (Scheuer's stage Ⅲ~Ⅳ) was 1.79% (LC vs non‐LC P < 0.001) . The ratio of HCC incidence for stage Ⅲ~Ⅳ/stageⅠ~Ⅱ was 6.88‐fold.…”
Section: Resultsmentioning
confidence: 96%
“…The annual incidence (%) of HCC in the non‐cirrhotic state (Scheuer's stage Ⅰ~Ⅱ) was 0.26% and that in the pre‐cirrhotic ~cirrhotic state (Scheuer's stage Ⅲ~Ⅳ) was 1.79% (LC vs non‐LC P < 0.001) . The ratio of HCC incidence for stage Ⅲ~Ⅳ/stageⅠ~Ⅱ was 6.88‐fold.…”
Section: Resultsmentioning
confidence: 96%
“…Symptoms of HCC include yellow skin, bloating from fluid in the abdomen, easy bruising from blood clotting abnormalities, loss of appetite, unintentional weight loss, nausea, vomiting and tiredness ( 5 , 6 ). The primary risk factors for HCC were hepatitis C, hepatitis B, alcoholism, aflatoxin and cirrhosis of the liver ( 7 10 ). Liver transplantation, tyrosine kinase inhibitors and surgical resection are currently the primary treatment options ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is by no means uncommon for PBC patients to suffer from hepatocellular carcinoma (HCC)[66-69]. Of two retrospective studies in China, one demonstrated an incidence of HCC in PBC patients of 4.13% (52/1255)[66], while the other found it to be 3.75% (70/1865)[67]; this incidence was observably higher in men (9.52%) than in women (3.31%)[66].…”
Section: Fat-soluble Vitamin Deficiencymentioning
confidence: 99%
“…Of two retrospective studies in China, one demonstrated an incidence of HCC in PBC patients of 4.13% (52/1255)[66], while the other found it to be 3.75% (70/1865)[67]; this incidence was observably higher in men (9.52%) than in women (3.31%)[66]. Risk factors for PBC-related HCC in China for the two studies were found to be body mass index (BMI) ≥ 25, male sex and a history of drinking alcohol for the first study[66] and age > 54 years, male sex, co-existence of diabetes, and previous hepatitis B virus (HBV) infection for the second study[67]. A retrospective Japanese study found the incidence of HCC in PBC patients to be 5.2% (11/210), with the only risk factor for PBC-associated HCC being associated with advanced histological stage[68].…”
Section: Fat-soluble Vitamin Deficiencymentioning
confidence: 99%